Impacts of renewable portfolio standard on carbon emission peaking and tradable green certificate market: A system dynamics analysis method - Zhang, Yidi; Deng, Hui; Yang, Jiajia; Xu, Chengwei; Zhou, Ziqing; Wen, Fushuan; Qi, Donglian (Frontiers in Energy Research, 2022)
With the announcement of the carbon peaking and carbon neutrality target in China as well as the launch of the nationwide green power renewable generation trading, one of the key issues is how to design an effective renewable portfolio standard (RPS) and build an efficient tradable green certificate (TGC) market. The quota that stipulates the share of electricity supplied from qualified renewable energy (RE) sources has substantial impacts on the TGC market, the electricity market, and the occurred time of carbon emission peaking. However, few studies have been reported on effectively quantifying the impacts of quota variation. Given this background, this paper presents an innovative system dynamics (SD) model to evaluate the impacts of quota variation on the trading results of the TGC market and the trend of carbon emissions in China for the next decade. The proposed SD model takes factors such as the accommodating capability by the power system for RE generation, the policy-driven carbon emission reduction target as well as the decreasing fixed feed-in tariff (FIT) for RE generation as constraints for the first time. These factors are quantified in the constraints based on the current RE policies and market trading mechanism in China to improve the evaluation accuracy of the SD model. Using real-world data, simulations under various scenarios are carried out to validate the feasibility and efficiency of the proposed model. The methods for further improving the design of TGC market are also further explored, which are expected to effectively guide China to achieve the carbon peaking target.